Georgia's Charter of 1732 - Barnes, Roy (Georgia Open History Library, 1942)
Georgia's Charter of 1732, originally published in 1942, is a scholar's guide to the charter. The full text of the Georgia Charter of 1732 is reproduced in the book alongside the Albert B. Saye's account of the events leading up to the granting of the charter. This essential moment at the very beginning of Georgia's history is better understood through Saye's narrative surrounding the Georgia Charter. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.